THE INFLUENCE OF DIGITAL MARKETING, BRAND AMBASSADOR, AND PRICE ON ERIGO PRODUCT PURCHASE DECISION - Duta Herzego Putra; Ayu Nurafni Octavia; Priyo Aji Laksono (International Journal of Management, Business, and Social Sciences, 2024)
This research is based on the decline of the Erigo Brand as the Top Local Clothing Brand in 2021 to 2022 by 2.9 percent. So research is needed to improve purchasing decisions influenced by digital marketing, brand ambassadors, and Erigo brand prices carried out in the World's Best JKT48 Community. This research was conducted using a survey method among members of the World's Best JKT48 Community who are members of the Discord server, totaling 94 respondents. Data collection was carried out using a questionnaire, and data analysis used SPSS 21 which includes validity, reliability, classical assumption testing, multiple regression analysis, and hypothesis testing. The research results show that digital marketing, brand ambassador, and price have a positive and significant effect on purchasing decisions. Erigo needs to share digital content that better supports its product promotion to increase product purchasing decisions. Erigo needs to increase purchasing interest in product purchasing decisions through brand ambassadors who can further influence consumers. Erigo needs to consider new prices that better suit its products to improve purchasing decisions. The coefficient of determination value of 0.678 indicates that the purchasing decision variable can be explained by digital marketing, brand ambassador and price variables of 67.8% while the remainder is explained by other variables outside the research